The Comparative Analysis of Academic Performance of Music Students at Nkonya Senior High School - Agboga, Prosper Kofi; Selassie, Ahiabor (International Journal of Rehabilitation and Special Education (IJRSE), 2022)
The study compares the academic performance of music students at Nkonya Senior High School from 2011 to 2016 based on year groups. The goal of the study was to determine the courses, effects, recommended remedies, and measures put in place to improve academic performance. The data was collected and analyzed utilizing a qualitative and quantitative analysis (triangulation) study technique from October 2016 to February 2017. The study discovered that a lack of parental support, poverty, absenteeism, individual mental capacities, and the involvement of school officials all contribute to changes in academic performance. Boys were found to be missing more frequently in external examinations than girls, according to the data. However, when looking at overall academic achievement over a six-year period, boys outperform girls. The study suggests that music students, music teachers, and school administration all play important roles in raising the school’s academic level. This will maintain students’ interest in music and ensure that the student population in the subject continues to expand year after year. To ensure parity in academic achievement in following years, the music teacher should identify strategies to increase female students’ enthusiasm in the subject. Parents should also supply necessary academic resources and supervise children’s attendance to prevent truancy and absenteeism. This will enhance academic achievement of pupils at Nkonya Senior High School.
Keywords: Academic performance; Music; Students; Nkonya SHS; Academic achievement